Penerapan Metode Story Telling dalam Peningkatan Meaning Of Life pada Lansia di Day Care Aisyiyah Pekanbaru - Nova Yulita; Hendri K; Husna Farianti Amran (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Increasing Life Expectancy resulted in a significant increase in the number of elderly people. This condition requires quality elderly, namely elderly who are healthy, independent, active and productive. The older you get, the more likely a person is to experience physical and psychosocial problems. The psychosocial crisis experienced by the elderly can also cause an elderly person to experience a decrease in the meaning of his life. Even though the meaning of life is a fundamental need for everyone, including the elderly. One of the non-pharmaceutical intervention methods used to increase happiness and well-being in the elderly is storytelling. This study aims to apply the story telling method in increasing the meaning of life in the elderly. This type of quantitative research is one group pre-test post-test experiment with a cross-sectional approach. The population of all elderly people in Aisyiyah Riau Day Care March-April 2023 is 17 people. Data were collected using a questionnaire and analyzed univariately and bivariately with the Wilcoxon Signed Rank Test. Based on the research, it is known that there is an increase in the mean value (average value) of respondents in the pretest is 53.776 and the average value of respondents in the posttest is 60.7776. Based on bivariate analysis using the Wilcoxon sign rank test, it is known that there is a significant difference between the pretest and posttest results with a Z value: -2.731 with a P value (A-symp.Sig 2 tailed) 0.006 .